Personal characteristics, occupational stress and turnover intentions among school teachers in Negeri Sembilan, Malaysia - Salahudin, Shahrul Nizam; Abdullah, Muhammad Madi; Hitam, Sabihah; Idrus, Durrishah (2007)
Stress is considered as a serious problem in the modern workplace. This paper summarizes occupational stress and turnover intentions experienced by secondary school teachers in the state of Negeri Sembilan, Malaysia. The aim of this study is to investigate the differences across different personal characteristics of the teachers and their level of stress and turnover intention. A total of 150 self-administered questionnaires were collected from secondary schools in the state of Negeri Sembilan. The study reveals that there are significant differences between teachers’ personal characteristics with occupational stress and turnover intention. This study also revealed that there is a positive significant relationship between occupational stress and turnover intention experienced by these teachers. Based on the results, some recommendations are provided.